Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1037/a0018407
|View full text |Cite
|
Sign up to set email alerts
|

Dose effects of triazolam and alcohol on cognitive performance in healthy volunteers.

Abstract: Benzodiazepines and alcohol are widely used psychoactive substances that have performance-impairing effects. Research suggests that the impairment profiles for benzodiazepines and alcohol differ, though few cognitive psychopharmacological studies have directly compared these drugs. This double-blind, double-dummy, placebo-controlled, repeated measures study directly compared the acute dose effects of triazolam (0.125 mg, 0.25 mg/70 kg) and alcohol (0.40 g, 0.80 g/kg) in 20 social drinkers. At doses that produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
32
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 85 publications
9
32
1
Order By: Relevance
“…These findings are in agreement with other preclinical results on rotarod and loaded grid test performance (Sanger et al, 1996;Voss et al, 2003), and also correspond to findings in humans on body sway, information processing rate, immediate memory, and sustained attention (Kleykamp et al, 2010;van Steveninck et al, 1996;Wilkinson, 1995). Almorexant, on the contrary, showed no effects on forced motor performance in the rat.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are in agreement with other preclinical results on rotarod and loaded grid test performance (Sanger et al, 1996;Voss et al, 2003), and also correspond to findings in humans on body sway, information processing rate, immediate memory, and sustained attention (Kleykamp et al, 2010;van Steveninck et al, 1996;Wilkinson, 1995). Almorexant, on the contrary, showed no effects on forced motor performance in the rat.…”
Section: Discussionsupporting
confidence: 91%
“…The finding of longer RTs in high dose BZD users was in line with experimental research on short term BZD use and RT [6][7][8][9][10][11] as well as with an observational study which found longer RTs in anxious, high dose BZD users (1.2-4 DDD) than in healthy non-users [14]. However, in the latter study it was unclear, whether prolonged RTs were due to BZD intake or psychopathology.…”
Section: Discussionsupporting
confidence: 75%
“…In most of these studies, BZD administration prolonged RTs for a duration up to 6 weeks [6][7][8][9][10][11]. Only two small studies did not find prolonged RTs after BZD intake [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Beverage was administered in a covered opaque cup and consumed through a straw wrapped with an ALC-soaked band to mask olfactory and gustatory cues. In addition, 2 ml of 95% ALC was added into the straw to mask taste differences between beverages 27 . The order of the six drug conditions (METH 100%/PL, METH 150%/PL, METH 100%/ALC 0.25, METH 100%/ALC 0.50, METH 150%/ALC 0.25, METH 150%/ALC 0.50) followed a fixed, ascending order (as listed above) for the first three participants as a precaution to determine if dosing conditions were safe and tolerated.…”
Section: Methodsmentioning
confidence: 99%